2009
DOI: 10.1002/ddrr.46
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic variation, number competence, and mathematics learning difficulties in young children

Abstract: As a group, children from disadvantaged, low-income families perform substantially worse in mathematics than their counterparts from higher-income families. Minority children are disproportionately represented in low-income populations, resulting in significant racial and social-class disparities in mathematics learning linked to diminished learning opportunities. The consequences of poor mathematics achievement are serious for daily functioning and for career advancement. This article provides an overview of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
206
3
24

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(256 citation statements)
references
References 82 publications
5
206
3
24
Order By: Relevance
“…This is contrary to some other countries (cf. Jordan & Levine, 2009). Furthermore, the test-retest effect (a potential bias for intervention improvements) was controlled for in each of the three sub-studies at the group level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is contrary to some other countries (cf. Jordan & Levine, 2009). Furthermore, the test-retest effect (a potential bias for intervention improvements) was controlled for in each of the three sub-studies at the group level.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that children with low socio-economic status (SES) exhibit lower spontaneous development during the kindergarten year (Jordan et al, 2006) and that the growth rate of their math skills decreases in first grade (Jordan et al, 2007) and later grades . Children from low SES families tend to be over-represented among those diagnosed as having MD (Jordan & Levine, 2009). However, in some studies, early performance level has been shown to predict later achievement regardless of initial SES level (Duncan et al, 2007).…”
Section: Figure 2 Terminology Describing Risk Levels For Mathematics mentioning
confidence: 99%
See 1 more Smart Citation
“…Si bien una serie de investigaciones se centra en las características de los aprendizajes infantiles en relación al dibujo, la escritura o el conocimiento numérico en diversos NSE (véase, por ejemplo, Jordan & Levine, 2009;Korat & Levin, 2001;Salsa, 2012Salsa, , 2013Saxe et al, 1987), resta todavía conocer si estos contextos restringen el conocimiento precoz de los sistemas de representación en base a sus características gráficas y propiedades formales. Asimismo, resultaría relevante indagar si las propiedades específicas de los sistemas arbitrarios de culturas distintas influyen en la trayectoria y edad en que se desarrolla el reconocimiento y diferenciación de estos sistemas por parte de los niños.…”
Section: Discussionunclassified
“…Contactamos a los niños a través de sus instituciones educativas, cuatro jardines de infantes de gestión privada de la zona céntrica de la ciudad de Rosario (Santa Fe, Argentina), donde concurren niños de NSE medios. La restricción en el NSE se fundamenta en investigaciones previas que han documentado la influencia de esta variable en el conocimiento de dibujo, escritura y número (Jordan & Levine, 2009;Korat & Levin, 2001;Salsa, 2012;Saxe et al, 1987). Los niños no contaban con antecedentes de trastornos en su desarrollo cognitivo y/o del lenguaje, de acuerdo con los registros de las instituciones educativas.…”
Section: Participantesunclassified